Surgery of the Thyroid and Parathyroid Glands - Oertli, Daniel; Udelsman, Robert; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book is a unique in-depth and comprehensive reference that covers all surgically relevant thyroid and parathyroid diseases and presents the latest information on their management. International authorities discuss operative techniques and treatments in detail and explain the rationales for their favored approaches. The topics of this second edition include the description of surgically relevant pathologies, preoperative surgical evaluation, decision making, and operative strategies for the various thyroid and parathyroid diseases. In addition, experts present the molecular basis for thyroid neoplasia, review the current understanding of the genetics of inherited thyroid and parathyroid diseases, and discuss the management of recurrent and locally invasive thyroid cancer. Evolving modern operative techniques such as neuromonitoring and minimally invasive (videoscopic) approaches to the thyroid and parathyroids are also covered
From the Content: History of Thyroid and Parathyroid Surgery -- Embryology and Surgical Anatomy of the Thyroid and Parathyroid Glands -- Evaluation of Hyperthyroidism and Hyperthyroid Goiter -- Diagnostic Imaging of the Thyroid Gland -- Evaluation of Thyroid Nodes -- Fine-Needle Aspiration Cytology -- Molecular Diagnostic with FNA -- Benign Thyroid Goiter -- Surgery of Hyperthyroidims -- Thyroiditis -- Technique of Thyroidectomy -- Minimally Invasive Techniques in Thyroid Surgery -- Monitoring in Thyroid and Parathyroid Surgery - An Evidence-Based Balanced Approach -- Complications in Thyroid and Parathyroid Surgery -- Surgery for Solitary Thyroid Nodule Including Differentiated Thyroid Cancer -- Central Neck Dissection -- Modified Radical Neck Dissection -- Surgery for Medullary Thyroid Cancer -- Thyroid Lymphoma and Metastatic Lesions to the Thyroid -- Thyroid Pathology -- Radioactive Therapy and External Radiotherapy for Thyroid Cancer -- etc.
Keywords: Medicine; Surgery; Medicine & Public Health; Surgery